THE LEGACY THAT HAS COME DOWN TO US AS “JETI ASIRIM” - G.Kamalova; Muratbaeva Ayzada Akhmetovna (Лучшие интеллектуальные исследования, 2023)
Annotation: This article tells about the stages of development of Bakhshi and national music, about the many opportunities that are being created for the sphere of Bakhshi in the XXI century, as well as about the International Festival of Bakhshi.